Comparative morphology and species-groups of the oribatid mite genus Scapheremaeus (Acari: Oribatida: Cymbaeremaeidae), with new species from South Australia - Colloff, Matthew J. (Zootaxa, 2009)
The morphology of the genus Scapheremaeus Berlese, 1910 is reviewed and characters of taxonomic utility delineated. Based on the morphological review, some 13 species-groups are outlined based on major morphotypes. There are two main categories: i) species that have a complete circumdorsal scissure with plicate microsculpture on the circumnotogastral plate and strongly contrasting microsculpture (foveolae, ridges or tubercles) on the centrodorsal plate (plicate species-groups), and ii) species with the circumdorsal scissure complete, incomplete or absent but with little or no contrast in microsculpture between the central and lateral regions: typically both regions foveolate or reticulate (non- plicate species-groups). A catalogue of world species of Scapheremaeus is provided. Scapheremaeus petrophagus (Banks, 1906) is not a Scapheremaeus but belongs to an undetermined genus in the Ameronothroidea. Cymbaeremaeus cyclops Oudemans, 1915 is recombined to Scapheremaeus. Five new species are described (S. angusi sp. nov., S. cheloniella sp. nov., S. ewani sp. nov., S. lambieae sp. nov., and S. pulleni sp. nov.) from soil and litter habitats in semi-arid Mallee eucalypt vegetation at Bookmark Biosphere Reserve, South Australia. These are the first members of the genus Scapheremaeus to be described from Australia, though undescribed species have been recorded previously. All the new species are morphologically closely-related and belong to a single species-group: Carinatus.